Why medieval philosophy matters - Boulter, Stephen (Why philosophy matters., 2019)
Tackling the question of why medieval philosophy matters in the current age, Stephen Boulter issues a passionate and robust defense of this school in the history of ideas. He examines both familiar territory and neglected texts and thinkers whilst also asking the question of why, exactly, this matters or should matter to how we think now. Why Medieval Philosophy is also provides a introduction to medieval philosophy more generally exploring how this area of philosophy has been received, debated and, sometimes, dismissed in the history of philosophy.--Back cover.